2020
DOI: 10.4102/sajcd.v67i2.669
|View full text |Cite
|
Sign up to set email alerts
|

Burden of disease: A scoping review of HIV/AIDS and TB in occupational noise-induced hearing loss

Abstract: Background: Occupational noise-induced hearing loss (ONIHL) does not occur in isolation from other influencing factors such as health conditions and illnesses like human immunodeficiency virus and acquired immunodeficiency syndrome (HIV and AIDS), as well as tuberculosis (TB). How the burden of disease influences the occurrence and/or management of ONIHL becomes a key if the goal of hearing conservation programmes (HCPs) is to be achieved within these contexts.Objectives: The purpose of this scoping review was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Tangiisuran et al (2009) reported that not all nurses, pharmacists, clinicians or patients have the capacity to accurately recognise adverse drug reactions for numerous reasons, including expectations, education and previous experience, and this observation is true for ototoxicity in the South African context (Bardien et al 2009;De Andrade et al 2009;Govender et al 2020 Wium & Gerber 2016). With ototoxicity in the elderly, this reality is additionally obscured by the presentation of ototoxicity, which is often non-specific and atypical or presents similarly to other common causes of hearing loss such as ONIHL or presbycusis, where the symptoms might be understood as a primary rather than secondary diagnosis that is a result of medication , 2020c. Rochon and Gurwitz (1997) cautioned about the challenge caused by this inability to identify adverse drug reactions precisely and differentiate drug-induced symptoms from a conclusive medical diagnosis, in that it leads to the prescription of yet additional drugs to manage the symptoms, which raises adverse drug reactions and drug-drug interactions, referred to as 'the prescribing cascade'.…”
Section: Adult Populationmentioning
confidence: 99%
“…Tangiisuran et al (2009) reported that not all nurses, pharmacists, clinicians or patients have the capacity to accurately recognise adverse drug reactions for numerous reasons, including expectations, education and previous experience, and this observation is true for ototoxicity in the South African context (Bardien et al 2009;De Andrade et al 2009;Govender et al 2020 Wium & Gerber 2016). With ototoxicity in the elderly, this reality is additionally obscured by the presentation of ototoxicity, which is often non-specific and atypical or presents similarly to other common causes of hearing loss such as ONIHL or presbycusis, where the symptoms might be understood as a primary rather than secondary diagnosis that is a result of medication , 2020c. Rochon and Gurwitz (1997) cautioned about the challenge caused by this inability to identify adverse drug reactions precisely and differentiate drug-induced symptoms from a conclusive medical diagnosis, in that it leads to the prescription of yet additional drugs to manage the symptoms, which raises adverse drug reactions and drug-drug interactions, referred to as 'the prescribing cascade'.…”
Section: Adult Populationmentioning
confidence: 99%
“…Tangiisuran et al (2009) reported that not all nurses, pharmacists, clinicians or patients have the capacity to accurately recognise adverse drug reactions for numerous reasons, including expectations, education and previous experience, and this observation is true for ototoxicity in the South African context (Bardien et al 2009;De Andrade et al 2009;Govender et al 2020 Wium & Gerber 2016). With ototoxicity in the elderly, this reality is additionally obscured by the presentation of ototoxicity, which is often non-specific and atypical or presents similarly to other common causes of hearing loss such as ONIHL or presbycusis, where the symptoms might be understood as a primary rather than secondary diagnosis that is a result of medication , 2020c. Rochon and Gurwitz (1997) cautioned about the challenge caused by this inability to identify adverse drug reactions precisely and differentiate drug-induced symptoms from a conclusive medical diagnosis, in that it leads to the prescription of yet additional drugs to manage the symptoms, which raises adverse drug reactions and drug-drug interactions, referred to as 'the prescribing cascade'.…”
Section: Adult Populationmentioning
confidence: 99%
“…Current reports suggest that there is approximately 40 million people living with HIV globally, with LMICs continuing to be the epicenter for the pandemic. In countries such as South Africa, HIV contribute to burden of diseases [ 2 ] and forms part of the quadruple burden of diseases [ 3 ], over and above a dilapidated health system [ 4 ], high levels of unemployment rates and poverty [ 5 ].…”
Section: Introductionmentioning
confidence: 99%